2017
DOI: 10.1007/s11418-017-1145-y
|View full text |Cite
|
Sign up to set email alerts
|

18β-glycyrrhetinic acid inhibits migration and invasion of human gastric cancer cells via the ROS/PKC-α/ERK pathway

Abstract: 18β-glycyrrhetinic acid (18β-GA) is a bioactive component of licorice root which exerts pharmacological activities including anti-inflammatory, antiviral, anti-oxidative and anti-cancer effects. The current study further investigated the molecular mechanisms associated with the inhibitory effects of 18β-GA on tumor metastasis in human gastric cancer cells. The results indicated that 18β-GA significantly reduced invasion and migration activities and suppressed MMP-2 and 9 activities on SGC-7901cells in a dose-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…A study indicated that TBL-12, a sea cucumber extract, inhibits migration and invasion of human PCa cells by inhibiting MMP-2 and MMP-9 via decreased phosphorylation of p38 ( 46 ). Additionally, 18β-glycyrrhetinic acid inhibits migration and invasion of gastric cancer cells via the reactive oxygen species/protein kinase C-α/ERK signaling pathway ( 47 ). Therefore, the present study investigated whether the MAPK pathway is altered by pinosylvin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A study indicated that TBL-12, a sea cucumber extract, inhibits migration and invasion of human PCa cells by inhibiting MMP-2 and MMP-9 via decreased phosphorylation of p38 ( 46 ). Additionally, 18β-glycyrrhetinic acid inhibits migration and invasion of gastric cancer cells via the reactive oxygen species/protein kinase C-α/ERK signaling pathway ( 47 ). Therefore, the present study investigated whether the MAPK pathway is altered by pinosylvin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the published data described the ability of GA and its derivatives to inhibit tumor cell motility, playing a crucial role in metastasis [ [43][44][45][46], we hypothesized that compound 5f can modulate this process in HeLa cells. To test this, we evaluated the effect of the nontoxic concentration of 5f on the migratory capacity of HeLa cells in real time mode.…”
Section: Compound 5f Inhibits the Metastatic Potential Of Hela Cells mentioning
confidence: 99%
“…EDNRB antibodies for Western blotting (ab117529) and flow cytometry (ab129102) and GAPDH antibody for Western blotting (ab9485) [31] were purchased from Abcam (Cambridge, United Kingdom). pERK (#4370) and ERK (#4695) [32] antibodies, along with pan AKT (4691), phospho AKT T308 (13038) and phospho-AKT1 S473 and phospho-AKT2 S474 (8599) were all purchased from Cell Signaling (Cell Signaling Technology, Beverly, MA). Secondary antibodies, including goat anti-mouse IgG-HRP, goat anti-rabbit IgG-HRP, goat anti-rabbit IgG-FITC were all purchased from Cell Signaling.…”
Section: Chemicals Nucleic Acids Plasmids and Antibodiesmentioning
confidence: 99%